ANALISIS PENGALAMAN PENYEBAB KONFLIK PADA MANTAN TENAGA KERJA WANITA YANG PERNAH BEKERJA DI HONGKONG - Linda Veronika (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Migrant workers are considered as one of main incentives for Indonesian economy. It’s shown through a report shows that the biggest foreign exchange comes from the workers that work in Hongkong. However, the worker often faces any conflicts happened due to their lack of knowledge. It’s caused by their inability to learn about the language. Besides, the cultural differences occurred between Indonesia and Hongkong make the worker hard to adapt. This research uses theory that is related with several aspects such as, cause of conflict, kind of conflict, effect of conflict, and how to solve it. This research uses qualitative approach and case study with indept interview which is conducted through the source. The results of this study are two researchers did not master the language, so it can lead to misunderstandings in communication.